The art of entrepreneurship : the proactive method to turn the time, talent, and resources you have into what you want - Stovall, Jim; Schneider, Kevin (Sound Wisdom, 2022)
"Entrepreneurship is both a science and an art. This book teaches both dimensions--the hard skills and the soft skills, the action steps and the mindset--so that you can seize the opportunities for entrepreneurship in your midst and turn your business idea into a successful start-up that adds value to you, your family, your community, and the larger world." --supplied by publisher.